Dynamic behaviour of auxetic gradient composite hexagonal honeycombs. (1st August 2016) - Boldrin, L.; Hummel, S.; Scarpa, F.; Di Maio, D.; Lira, C.; Ruzzene, M.; Remillat, C.D.L.; Lim, T.C.; Rajasekaran, R.; Patsias, S.
Abstract: The paper describes a vibroacoustics analysis of auxetic gradient honeycomb composite structures with hexagonal configurations. We examine two classes of gradient cellular layout – one with continuously varying internal cell angle, the other with gradient cell wall aspect ratio across the surface of the honeycomb panel. The structural dynamics behaviour of the two gradient honeycomb configurations is simulated using full-scale Finite Elements and Component Mode Synthesis (CMS) substructuring. Samples of the gradient honeycombs have been manufactured by means of 3D printing techniques, and subjected to modal analysis using scanning laser vibrometry. We observe a general good comparison between the numerical and the experimental results. A numerical parametric analysis shows the effect of the gradient topology upon the average mobility and general vibroacoustics response of these particular cellular structures.